Shiga toxin-producing Escherichia coli (STEC) and Salmonella spp. in lettuce (Research, Society and Development, 2020)
Foodborne illnesses are relevant to public health, especially in contaminated foods that are eaten without prior cooking, such as lettuce. The objective was to evaluate the contamination by Shiga toxin-producing Escherichia coli (STEC), E. coli and Salmonella spp. in lettuce in commercial food-establishments in the city of Jataí, Goiás, Brazil. The variables were: type of crop, type of establishment and coliform count. The DNA of E. coli isolates were analyzed by PCR to the research of virulence genes. Isolates compatible with Salmonella in the biochemical tests were submitted for serology with Salmonella antisera. Thirty samples of lettuce were evaluated, eleven samples were positive for E. coli, (36.67%), and one sample (3.33%) tested positive for STEC hydroponic crop. The two STEC isolates were positive for the stx2 gene. Conventionally grown products were 2.4 times more likely to be contaminated with E. coli. The presence of Salmonella spp. was confirmed in 16.67% (5/30) of the samples. The presence of potentially pathogenic microorganisms in the analyzed samples indicates the need for special care to be taken in preparing fresh vegetables before they are consumed in natura, like avoid excessive handling, and washing with sanitizers.